VERTICAL AND HORIZONTAL METAMORPHOPSIA ONE YEAR AFTER SURGERY FOR MACULAR HOLES ≤ 500 µ m WITH AND WITHOUT INVERTED INTERNAL LIMITING MEMBRANE FLAP - Baumann, Carmen; Maier, Mathias; Johannigmann-Malek, Navid; Gabka, Katharina; Schwer, Lydia; Kaye, Stephen B (Retina (Philadelphia, Pa.), 2024)
To investigate the effect of an inverted internal limiting membrane flap (IF) and other factors on metamorphopsia after macular hole surgery. Prospective case series of patients undergoing pars plana vitrectomy with gas tamponade, with either conventional internal limiting membrane peeling (CP) or an IF, for primary idiopathic macular holes ≤ 500 µ m. Vertical and horizontal metamorphopsia were measured as M-scores (degrees) using M-charts preoperatively and at 2, 6, and 12 months postoperatively. Fifty-three eyes of 53 patients were included of whom 27 underwent CP and 26 were treated with an IF. After macular hole surgery, all patients were pseudophakic. Vertical and horizontal metamorphopsia improved from 1.08 (±0.51) and 0.98 (±0.70) preoperatively to 0.58 (±0.37) and 0.45 (±0.36) at 2 months ( P < 0.01), with no further significant improvement at 6 months (0.39 [±0.31], P = 0.07 and 0.31 [±0.28], P = 0.18) or at 12 months (0.37 [±0.30], P = 0.72 and 0.28 [±0.28], P = 0.99). There was no significant difference in the mean vertical and horizontal metamorphopsia between patients with CP and with an IF at 2 months ( P = 0.063, P = 0.10), 6 months ( P = 0.25, P = 0.16), or 12 months ( P = 0.62, P = 0.22). Preoperative vertical M-score improved at 12 months after macular hole surgery by 61% and 64% in the CP and IF groups, respectively ( P = 0.84), and the horizontal M-score by 65% and 71%, respectively ( P = 0.98). The use of an IF has no evident bearing on the degree of postoperative metamorphopsia 12 months after surgical repair of macular holes ≤ 500 µ m.